Audience Award, for the video But at the End the Light was Shed on us and it Got us to the Shore”, - Antoniou, Klitsa (My University, 2026)
Audience Award, for the video “But at the End the Light was Shed on us and it Got us to the Shore”, Mykonos MultiMedia Biennale, Migration Section.
Keywords: Arts and entertainment